THE USE OF INSTAGRAM AS A PROJECT BASED LEARNING: STUDY EXPERIMENTAL AT JUNIOR HIGH SCHOOL - pratama, Aryawira; Daryani, Lilis (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
This research aims to find the effect of Project Based Learning techniques on students' writing skills. The Project Based Learning that is used in this research was Instagram for writing skill. The material was limited by descriptive text which exist on eighth grade in junior high school. This research was design by pre-experimental method which consist of two classes. The participants was chosen by random sampling which separated into class VIII A as the experimental class and VIII B as the control class at SMP Negeri 26 Sarolangun. Total meeting of doing this experimental is seven meetings including pre-test, treatment and post-test. The result of this study was significance. It showed by the result of paired sample t test, the value was 0.001 â‰¤ 0.05. It denotes Ha's acceptance. Therefore, posting on Instagram about student writing suggests that project-based learning has a big impact.